The Influence of Emotional Intelligence, Job Satisfaction, and Work Engagement on the Performance of Employees in the Labuhanbatu Regency’s Youth, Sports, Culture, and Tourism Services - Sahmuddin Sahmuddin; Zulkifli Musannip Efendi Siregar; Fauziah Hanum (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2022)
This research aims to analyze the influence of emotional intelligence, job satisfaction, and work engagement on employee performance Department of Youth, Sports, Culture and Tourism, Labuhanbatu Regency. The population in this study was 70 people. The sampling technique uses saturated sampling. The sample size in this study was 70 people. The data collection method uses questionnaires. The results of multiple linear regression analysis obtained the equation Y = 3.457 + 0.356X1 + 0.372X2 + 0.253X3. In the partial test (t test) the regression coefficient of the emotional intelligence variable (X1) obtained a calculated t value of 2.473 > t table 1.996 which means that the variable emotional intelligence has a positive and significant effect on employee performance variables with a significant value of 0.016 < 0.05. The regression coefficient for the job satisfaction variable (X2) obtained a calculated t value of 3.161 > t table 1.996, which means that the job satisfaction variable has a positive and significant effect on the employee performance variable with a significant value of 0.002 < 0.05. The regression coefficient for the work engagement variable (X3) obtained a calculated t value of 2.480 > t table 1.996, which means that the work engagement variable has a positive and significant effect on the employee performance variable with a significant value of 0.016 < 0.05. The results of the F test obtained Fcount value of 32.244 > Ftable 2.74 with a significance value of 0.000 < 0.05, so it can be concluded that emotional intelligence, Job satisfaction, and work engagement simultaneously have a positive and significant effect on employee performance. The coefficient of determination test results show that the variables of emotional intelligence, job satisfaction, and work engagement have as much influence as 59.4% on employee performance variables, while the remaining 40.6% is influenced by other variables outside this research.